تعريف بعض الأنواع من فصيلة ذباب السرفيد (Diptera: Syrphidae) في منطقة اللاذقية - أحمد, محمد; منصور, علي; العش, ديما (Latakia University Journal -Biological Sciences Series, 2018)
أجريت هذه الدراسة خلال الفترة من 10/9/2016 حتى9/9/2017 في منطقة بساتين دمسرخو (اللاذقية) الواقعة على الساحل الغربي للجمهورية العربية السورية, وهدفت إلى حصر أولي لأنواع ذباب السرفيد المتواجد في هذه المنطقة. جُمعت العينات بطريقة الأطباق الصفراء أسبوعياً. تم خلال هذه الدراسة جمع341 عيّنة من بالغات ذباب السرفيد, عرِّف 15نوعاً تتبع لـِ 10 أجناس, وكان النوع scripta Sphaerophoria ذو الغزارة النسبية الأعلى (33.43%), تلاه النوع Episyrphus balteatus (20.53%), ثم النوعMelanostoma mellinum (14.66%). This study was conducted during the period from 10/9/2016 to 9/9/2017 in Demsarkho orchards area (Lattakia) on the west coast of Syrian Arab Republic. The study aimed to identificate "Syrphidae" in this area. Samples were collected by yellow dishes in weekly rate. A total of 341 Syrphid flies were collected and they belong to 15 species form 10 genera. The most abundant species was Sphaerophoria scripta (relative abundance 33.43%), followed by Episyrphus balteatus (20.53%), then Melanostoma mellinum (14.66%).